Wireless interrogation of an optically modulated resonant tunnelling diode oscillator - Cantú, H.; Salgado, H.; Romeira, B.; Kelly, A.; Ironside, Charlie; Figueiredo, J. (2013)
In this work, a resonant tunnelling diode-photo-detector based microwave oscillator is amplitude modulated using an optical signal. The modulated free running oscillator is coupled to an antenna and phase locked by a wireless carrier that allows remote extraction of the information contained in the modulation. An off-the-shelf demodulator has been used to recover the envelope of the baseband data originally contained in the optical signal. Data were successfully transmitted at a rate of 1 MSym/s with a bit error rate below 10-6. Copyright © 2013 Wiley Periodicals, Inc.